Two centuries of ornithological exploration of the Rio Doce Basin, southeastern Brazil. Part II—A catalogue of its birds and a gazetteer - Lopes, Leonardo Esteves; Baptista, Michelle Noronha Da Matta; Reis, Jéssica Naiara; Fernandes, Alexandre Mendes; Heming, Neander Marcel; Magnago, Gustavo; Nacif, José Augusto; Nogueira, Wagner; Rodrigues, Marcos; Vasconcelos, Marcelo Ferreira De (Zootaxa, 2024)
The Rio Doce Hydrographic Basin (RDB) lies almost completely in the Brazilian Atlantic Forest, a highly threatened tropical rainforest. The RDB has suffered dramatic anthropogenic impacts during the last two centuries and is currently one of the most degraded regions in southeastern Brazil. In this paper, we gathered 140,742 bird records collected since the early 19th by more than two thousand naturalists, professional scientists, and citizen scientists. This vast database was compiled from several sources, including published literature, unpublished technical reports, natural history museums, and citizen science platforms. After checking and standardizing the database, we found high species richness in the RDB, with 689 species recorded to date, from which 675 (98%) were documented by specimens or digital vouchers. This database is presented as a detailed catalogue, including maps containing all localities in which each species has been recorded. We present text accounts for 40 noteworthy species recorded in the RDB, and a complete gazetteer for the 636 localities sampled. Preliminary analyses reveal that the RDB avifauna suffered a dramatic change in its species composition during the last two centuries, mostly due to human activity. Highly sensitive species associated to pristine forests vanished, while species associated to dry and open habitat expanded their ranges in the RDB. Finally, in addition to thoroughly characterization of the RDB avifauna, this paper provides the basis for a series of studies about the avifauna of one of the hottest hotspots of biodiversity in the entire Neotropical region.